Study of Conformational Preferences of Erythro-Carolignan E Assessed By The Coupling Between H7'-H8' in Different NMR Solvents - Rudiyansyah Rudiyansyah; Ajuk Sapar; Masriani Masriani (ALCHEMY Jurnal Penelitian Kimia, 2015)
Erythro-carolignan E (1) has been obtained from the ethanol extract of the wood bark of Durio affinis Becc. This research was conducted in order to prove that conformational preferences of compound 1 were solvent dependent. On the basis of 1H-NMR data, the relative configuration of compound 1 was characterized by a coupling constant (3JHH) value of 3.3 Hz at H-7' in CDCl3. The coupling constant (3JHH) values of H-7' in compound 1 has changed to 4.1 Hz and 5.3 Hz in pyridine-d5 and acetonitrile-d3 respectively. As a result, the conformation of compound 1 at C7'-C8' has changed in different NMR solvents.  In conclusion, structure oferythro-carolignan E that contains a dihydroxy group at C7'-C8' is able to change in different NMR solvent.